(untitled) (Bangladesh Journal of Pharmacology, 2016)
The purpose of this study was to evaluate the effects of Pericampylus glaucus extract on plasma glucose concentration and lipid profile in normal and streptozotocin-induced diabetic rats. The ethanolic extract were administered orally at three different doses (400, 600 and 800 mg/kg) and glibenclamide (20 mg/kg p.o.) for 21 days after 72 hours of streptozotocin injection. During the short- and long-term studies, the extract was found to possess significant (p<0.01, p<0.001) anti-diabetic activity in normal and diabetic rats compared with untreated normal and untreated diabetic group. It also caused reduction in the level of total cholesterol, triglyceride, and LDL etc. and improvement in the HDL level compared with untreated diabetic rats. Reduction in the fasting blood sugar, cholesterol, triglyceride, urea, LDL, creatinine levels and improvement in the HDL by P. glaucus indicates that plant has anti-diabetic activity along with anti hyperlipidemic efficacy and provides a scientific rationale for the use.